Membedah Uji Prasyarat: Kunci Pemilihan Uji Hipotesis dalam Statistik Kuantitatif dan Panduan Cepat SPSS Uji Prasyarat Statistik - Risnawati; Hamdani, M. Fikri; Toedien, Faisal Amir (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2025)
This article comprehensively discusses assumption tests in statistical analysis, including the steps to implement them using SPSS software, along with examples of statistical test outputs. Assumption testing is a crucial early stage in quantitative research because it determines the feasibility of selecting statistical analysis techniques, especially in distinguishing between the use of parametric and non-parametric tests. Normality, homogeneity, and linearity tests are presented practically in this article to make understanding easier, especially for novice researchers. Additionally, this article briefly mentions the types of hypothesis tests commonly used in quantitative research and their test classifications. The approach used in writing this article is library research, in order to strengthen the theoretical basis and enrich the discussion. Hopefully, this article can be a useful conceptual reference for students, researchers, and practitioners in applying statistical analysis appropriately, systematically, and in accordance with scientific procedures.